ISLAMIC POPULISM AND THE QUESTION OF SECULARISM: INDONESIA AND TURKEY - Farhan Abdul Majiid (Pusat Riset Politik BRIN, 2023)
Turkey and Indonesia are among a few Muslim-majority countries that have embraced democratisation since their independence. While the development of their democracies is not linear and marred with periods of autocratic regimes, the debate over the position of Islam within the secular state has remained relevant throughout the history of the modern Indonesian and Turkish Republic. This article uses Comparative Historical Analysis to examine how the contention over Islam in politics has been utilised by populist groups espousing Islamic aspirations as their ideological basis. This article argues that the formation and success of Islamic populist currents in Turkey and Indonesia is not dictated by their specific political and economic conditions, but also by their different adoption of secularism. Comparative analysis of these two countries is conducted in two steps. First, I explain the specific historical trajectories of secularisation, democratisation, and state-building of both Turkey and Indonesia. Second, I contrast both countries to demonstrate how their diverging process of secularisation has impacted the political success of Islamic populism. This article concludes that a stricter adoption of Secularism in Turkey has, inadvertently, brought more decisive success to Turkish Islamic populist groups; on the other hand, the ambiguous secularisation in Indonesia has hindered its Islamic populist forces from enjoying a similar degree of success. A stricter adoption of Secularism in Turkey brings more decisive success to Islamic populist groups, while an ambiguous approach in Indonesia hinders the Islamic populist groups from enjoying the same success.